Polymethacrylic Acid Adsorption and the Aggregation Stability of Titanium Dioxide Suspensions - M.M. Soltys; Z.M. Yaremko; D.M. Nykypanchuk; L.B. Fedushynska; V.D. Havryliv (Adsorption Science & Technology)
The dependence of polymethacrylic acid adsorption on to two rutile samples of titanium dioxide on the adsorbent content in the system and the degree of neutralization of the macromolecules has been studied. A scheme for the adsorption and aggregation processes occurring under the experimental conditions employed has been proposed and a correlation between the extent of polyelectrolyte adsorption and the aggregation stability of the titanium dioxide suspensions established. The extent of adsorption decreased with increasing adsorbent content and this has been explained by the decrease in surface available for macromolecular adsorption. Such decreases can arise from coagulation processes as well as from incomplete redispersion of the titanium dioxide particles. It has been shown that the maximum stability of the titanium dioxide suspensions occurs at polyelectrolyte concentrations well below the concentration necessary for adsorption saturation. As the degree of neutralization of the macromolecules increased the extent of adsorption decreased, the aggregation stability of suspensions in the presence of low molecular weight polymethacrylic acid remaining unchanged while that in the presence of high molecular weight poly-acid molecules decreased. The results obtained have been discussed in conjunction with the properties of aqueous solutions of partially neutralized polymethacrylic acid and changes in the conformations of the macromolecules.